Microscopic Failure Mechanism Analysis of Rock Under Dynamic Brazilian Test Based on Acoustic Emission and Moment Tensor Simulation - Zhou, Zilong; Zhou, Jing; Zhao, Yuan; Chen, Lianjun; Li, Chongjin (Frontiers in Physics, 2021)
Dynamic tensile failure of rock is a main failure mode in deep underground engineering projects. The microscopic failure mechanism analysis of this failure mode plays a key role in dynamic disaster warning. Moment tensor inversion is a very well-known method to analyze failure mechanism. However, the acoustic emission (AE) event cannot be accurately distinguished in rock dynamics experiments at laboratory scale. Because there will be hundreds of AE events generated within 250 μs in one dynamic test. Therefore, moment tensor analyze is rarely applied in rock dynamic test with laboratory scale. In this paper, AE and moment tensor simulated with discrete element method (DEM) are introduced to analyze microscopic failure mechanism of rock under dynamic Brazilian test. Comparing the simulation results of AE and moment tensor with the simulation results of micro-crack with DEM, the moment tensor discriminant method can obtain mechanical mechanism and energy level of micro-crack. Furthermore, R, which is the ratio of isotropic and deviatoric components of the moment tensor, is used to analyze AE source mechanism. The implosion, shear and tension of AE source mechanism can better explain the evolution process of main axial crack and the shear failure zones of the Brazilian disc specimen under dynamic tensile simulation. These findings can contribute to a better understanding of These results show that the moment tensor simulation is more intuitive and accurate to analyze the microscopic failure mechanism of rock under dynamic tensile test than the statistical types of micro-cracks based on break bond with DEM.